2021
DOI: 10.3389/fvets.2021.645667
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Cannabidiol (CBD)-Containing Treats Did Not Affect Canine Daily Voluntary Activity

Abstract: Growing public interest in the use of cannabidiol (CBD) for companion animals has amplified the need to elucidate potential impacts. The purpose of this investigation was to determine the influence of CBD on the daily activity of adult dogs. Twenty-four dogs (18.0 ± 3.4 kg, 9 months−4 years old) of various mixed breeds were utilized in a randomized complete block design with treatments targeted at 0 and 2.5 mg (LOW) and at 5.0 mg (HIGH) CBD/kg body weight (BW) per day split between two treats administered afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Currently in the veterinary literature, clinical effects in osteoarthritis and refractory seizures suggests that a dose of approximately 2–2.5 mg/kg every 12 to 24 h shows clinical efficacy which were the tenants of dosing in our study ( 6 , 8 , 9 , 15 , 19 , 26 , 28 , 29 ). While no benefit was identified in this present study, interestingly a recent abstract using the same product used in this study at a 5 mg/kg dose every 8 h may decrease pain scores in patients undergoing intervertebral disk disease surgery ( 30 ).…”
Section: Discussionmentioning
confidence: 78%
“…Currently in the veterinary literature, clinical effects in osteoarthritis and refractory seizures suggests that a dose of approximately 2–2.5 mg/kg every 12 to 24 h shows clinical efficacy which were the tenants of dosing in our study ( 6 , 8 , 9 , 15 , 19 , 26 , 28 , 29 ). While no benefit was identified in this present study, interestingly a recent abstract using the same product used in this study at a 5 mg/kg dose every 8 h may decrease pain scores in patients undergoing intervertebral disk disease surgery ( 30 ).…”
Section: Discussionmentioning
confidence: 78%
“…However, since the endocannabinoid system is a signaling pathway that regulates several actions, its interaction with different endogenous ligands and neurotransmitter modulation can have beneficial effects on patients suffering from seizures, contact and atopic dermatitis, epilepsy, degenerative myelopathies, asthma, diabetes, glaucoma, retinitis pigmentosa, and inflammatory diseases. These compounds also possess antineoplastic, appetite-stimulating, and antiemetic properties (3,90,(113)(114)(115)(116).…”
Section: Discussionmentioning
confidence: 99%
“…14 Studies testing the safety of short-term CBD use in dogs dosed PO with broad-spectrum hemp extracts at dosages ranging from 2 to 20 CBD mg/kg/day for 2 to 12 weeks reported either no or only mild AEs. 16,22,[33][34][35][36][37] In our study, the only AE noted in dogs supplemented with the highest dose was the higher frequency of soft feces or diarrhea with tenesmus and straining. In another study, diarrhea was a reported AE in dogs receiving oil-based CBD extract, but the study lacked a negative control group, 33,36 and thus no clear conclusions could be made.…”
Section: Adverse Eventsmentioning
confidence: 99%